Assessing the Efficacy of Cardiac Catheterization in Enhancing Blood Circulation in Patients with Coronary Heart Disease: A Systematic Literature Review - Sari, Khomariyana Purnama (Sriwijaya Journal of Internal Medicine, 2024)
Introduction: Cardiac catheterization is a highly efficient treatment for enhancing blood circulation to the heart in individuals with coronary heart disease (CHD). This operation has the potential to alleviate angina, enhance quality of life, and mitigate the likelihood of myocardial infarction. The objective of this study is to investigate the efficacy of cardiac catheterization in enhancing blood circulation among individuals suffering from CHD. Methods: We conducted a literature search on multiple databases, including PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to investigate the efficacy of cardiac catheterization in enhancing blood circulation among individuals diagnosed with CHD. This study adheres to the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Guidelines. Results: We identified twenty papers that satisfied the inclusion criteria in this investigation. The research articles were published between 2013 and 2023. The study analysis demonstrates that cardiac catheterization is efficacious in enhancing blood circulation in individuals with CHD. Cardiac catheterization can augment myocardial perfusion by up to 20%. Conclusion: Cardiac catheterization is more successful in individuals who have mild or moderate stenosis of the coronary arteries. The study analysis indicates that cardiac catheterization is efficacious in enhancing blood circulation in individuals with CHD.